The optical nonlinearity of Au and Ag nanoparticle prepared by the γ-radiation method - Shahriari, Esmaeil; Mat Yunus, Wan Mahmood; Naghavi, Kazem; Saion, Elias (Science Publications, 2010)
Problem statement: The third order nonlinear optical properties of metal nanoparticles have been of interest in physical chemistry, medical diagnostics and optical devices. Gold colloidal nanoparticles are responsible for the brilliant reds seen in stained glass windows and silver particles are typically yellow. The purpose of the study was to determine the nonlinear refraction and absorption coefficient of the Au and Ag nanoparticles in PVP solution.